2021
DOI: 10.3390/ijerph18189790
|View full text |Cite
|
Sign up to set email alerts
|

Incarceration and COVID-19: Recommendations to Curb COVID-19 Disease Transmission in Prison Facilities and Surrounding Communities

Abstract: Overcrowding can increase the risk of disease transmission, such as that of SARS-CoV-2 (COVID-19), within United States prisons. The number of COVID-19 cases among prisoners is higher than that among the general public, and this disparity is further increased for prisoners of color. This report uses the example case of the COVID-19 pandemic to observe prison conditions and preventive efforts, address racial disparities for people of color, and guide structural improvements for sustaining inmate health during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Consistent with recommendations for reducing disease transmission (Natoli et al, 2021) and effective COVID-19 prevention strategies identified in a recent systematic review (Esposito et al, 2022), EXIT-CJS study sites implemented a variety of policies to reduce the spread of COVID-19, including change in movement policies, elimination of in-person visitations, and a reduction in face-to-face medical visits. These policies impacted models of care for individuals with OUD, and additionally affected ongoing research in both carceral and community settings.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Consistent with recommendations for reducing disease transmission (Natoli et al, 2021) and effective COVID-19 prevention strategies identified in a recent systematic review (Esposito et al, 2022), EXIT-CJS study sites implemented a variety of policies to reduce the spread of COVID-19, including change in movement policies, elimination of in-person visitations, and a reduction in face-to-face medical visits. These policies impacted models of care for individuals with OUD, and additionally affected ongoing research in both carceral and community settings.…”
Section: Discussionmentioning
confidence: 92%
“…Coupled with economic challenges and job losses, community programs providing housing resources in the US experienced an increased demand for services (Pixley et al, 2021). In addition to demands on community services due to COVID-19, re-entry support systems may be overburdened due to moderately increased numbers of incarcerated persons being released into the community because of COVID-19 (Natoli et al, 2021;Prison Policy Initiative, 2022). Employment and housing are critical to successful reintegration into the community (Shinkfield & Graffam, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In many countries, responsibility for the provision of health care in prisons lies with the Ministry of Justice or the Ministry of the Interior and the Ministry of Health, which is why coordination and collaboration between the health and justice sectors is necessary to protect the health of people in prisons and thus reduce the disparities and health inequities experienced by prisoners in facing future outbreaks of COVID-19 in a carceral setting ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support recommendations from public health professionals and advocacy groups to reform crisis responses strategies by centering (1) population decompression, (2) improvement of living conditions through external oversight, and (3) incorporation of input from incarcerated people and their families. 27,28 Importantly, the American Public Health Association has called for wide-spread population decompression due to the well-documented harms associated with incarceration which have only been exacerbated by the pandemic. 27 Their comprehensive recommendations include use of diversion programs, sentencing, misdemeanor and bail reform.…”
Section: Discussionmentioning
confidence: 99%